Pathogenic fungi and oomycetes causing dieback on Fraxinus species in the Mediterranean climate change hotspot region - Benigno, Alessandra; Bregant, Carlo; Aglietti, Chiara; Rossetto, Giovanni; Tolio, Beatrice; Moricca, Salvatore; Linaldeddu, Benedetto T. (Frontiers in Forests and Global Change, 2023)
Environmental changes are occurring on a global scale, but their effects are most pronounced in climate change hotspot zones, such as the Mediterranean basin. Within this area Italy, extending from its southern coasts in the core of the Mediterranean Sea to its northernmost pre-Alpine and Alpine regions, is characterized by a variety of climatic conditions and vegetation types. Surveys conducted in 2018–2022 in forest formations of Central-Northern Italy revealed that the enhanced warming trend and irregular distribution of precipitations are strongly impacting the health of Fraxinus species, with some pathogenic fungi and oomycetes being important contributing factors to the decline of the three main ash species growing there: common ash (Fraxinus excelsior), flowering ash (Fraxinus ornus), and narrow-leaved ash (Fraxinus angustifolia). Isolation from symptomatic plant material collected countrywide under different site conditions and pathogenicity tests revealed a complex phytopathological framework, with several pathogenic species in addition to Hymenoscyphus fraxineus involved with a prominent role in the ash dieback etiology. Key microbial taxa included the fungal and oomycete pathogens Botryosphaeria dothidea, Diplodia fraxini, Diplodia subglobosa, Phytophthora acerina, and Phytophthora plurivora. The disease impact was higher on sites where ash trees grew under environmental stress (i.e., areas characterized by mild dry winters, hot summers with intense and prolonged drought) and exhibited reduced vigor, also as a consequence of anthropogenic interference (i.e., silvicultural management and fires). The identified causative agents are emerging pathogens that thrive under warmer conditions, their impact in the investigated areas being prevalent compared to H. fraxineus, which appears to be restricted on the Italian peninsula to the cooler and wetter valleys of the Alps and Central-Northern Apennines.